2002
DOI: 10.2165/00007256-200232130-00003
|View full text |Cite
|
Sign up to set email alerts
|

Resistance Training and Cardiac Hypertrophy

Abstract: Resistance training (RT) is a popular method of conditioning to enhance sport performance as well as an effective form of exercise to attenuate the age-mediated decline in muscle strength and mass. Although the benefits of RT on skeletal muscle morphology and function are well established, its effect on left ventricular (LV) morphology remains equivocal. Some investigations have found that RT is associated with an obligatory increase in LV wall thickness and mass with minimal alteration in LV internal cavity d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
46
0
6

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(62 citation statements)
references
References 51 publications
5
46
0
6
Order By: Relevance
“…Exercise is known to be a potent cardiac hypertrophic stimulus, but the magnitude and pattern of left ventricular hypertrophy is dependent on the nature, duration, and intensity of exercise (Pluim et al, 2000;Haykowsky et al, 2002). In the heart, there are different morphological adaptations to resistance and aerobic training.…”
Section: Discussionmentioning
confidence: 99%
“…Exercise is known to be a potent cardiac hypertrophic stimulus, but the magnitude and pattern of left ventricular hypertrophy is dependent on the nature, duration, and intensity of exercise (Pluim et al, 2000;Haykowsky et al, 2002). In the heart, there are different morphological adaptations to resistance and aerobic training.…”
Section: Discussionmentioning
confidence: 99%
“…The results of the early echocardiographic examinations made researchers postulate that the type of LV hypertrophy is dependent on the training regimen applied, with clear differences between athletes, devoted to extensive training intended to increase aerobic capacity, and sprint/power athletes who train mainly (to increase) muscle strength/power instead of aerobic (cardiovascular) capacity. It was suggested that intense (anaerobic, strength/power, or sprint) exercise training results in more concentric LV hypertrophy, which is characterized by an increase in LV mass with augmented ratio of wall thickness to the LV diameter as well (Haykowsky et al 2002); whereas, voluminous isotonic (aerobic or endurance) exercise training results in more prominent enlargement of LV diameter (Morganroth et al 1975;Snoeckx et al 1982;Fagard 2003). This variation in cardiac structure could be attributed to different haemodynamic loading conditions (such as stroke volume, heart rate, and arterial blood pressure) during sprint versus endurance training.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of the studies were performed on male athletes (Fagard 2003;Haykowsky et al 2002). Female athletes are believed to possess less pronounced cardiac size changes due to exercise training, which may be related to less arduous training and/or their hormonal environment (George et al 1999).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, very little is known about the signaling pathways that mediate cardiac and skeletal muscle adaptation to resistance training. For example, some studies showed that resistance training increases left ventricular (LV) cavity dimensions, septal and posterior wall thickness, and cardiac mass (12,19); other studies in short-and long-term resistance-trained athletes demonstrated no changes in LV morphology or mass (19,20). The inconsistency of these data probably reflects the fact that the cardiac response to resistance exercise is likely to depend on the duration (long term vs. acute) and type (bodybuilding, power lifting, or high intensity) of training regimen.…”
mentioning
confidence: 99%